The Effect of Ice Encasement and Protective Covers on the Winter Survival of Six Turfgrass Species on Putting Greens. Issue 1 (19th October 2017) - Waalen, Wendy M.; Espevig, Tatsiana; Kvalbein, Agnar; Aamlid, Trygve S.
Abstract : Ice encasement (IE) is the most economically important winter stress in Scandinavia; however, little is known about the IE tolerance of different turfgrass species and subspecies except that creeping bentgrass ( Agrostis stolonifera L.) is more tolerant than annual bluegrass ( Poa annua L.). The objective of this study was to assess the impact of IE and two protective covers (plastic and plastic over a 10‐mm woven mat) on the winter survival of six cool‐season turfgrasses commonly used on golf greens. The experiment was conducted on a sand‐based green at Apelsvoll, Norway (60°42′ N, 10°51′ E) during the winters of 2011–2012 and 2012–2013. Turfgrass samples (8 cm in diameter, 10 cm deep) were removed from the plots at the time of cover installation and throughout the winter. The samples were potted and percent live turfgrass cover assessed after 21 d of regrowth in a growth chamber. Percent turfgrass cover, percent disease, and turfgrass quality were also registered in the field plots in spring. Results indicated that velvet bentgrass ( Agrostis canina L.) had superior tolerance to IE, surviving for 98 and 119 d of IE during the winters of 2011–2012 and 2012–2013, respectively. The order of IE tolerance in 2012–2013 was: velvet bentgrass > creeping bentgrass > Chewing's fescue ( Festuca. rubra L. ssp. commutata ), slender creeping red fescue ( F. rubra L. ssp. litoralis ) ≥ colonial bentgrass ( A. capillaris ) > annual bluegrass. Colonial bentgrass responded negatively to both protective covers in 2012 due to the development of Microdocium nivale. None of the species benefited from the plastic cover alone, compared with natural snow conditions. Annual bluegrass was the only species that benefited from plastic over a woven mat.